2018
DOI: 10.1111/gwao.12247
|View full text |Cite
|
Sign up to set email alerts
|

Knowing cows: Transformative mobilizations of human and non‐human bodies in an emotionography of the slaughterhouse

Abstract: This ‘emotionography’ of the slaughterhouse elucidates how the identities of both human and non‐human individuals are constructed by line and lairage workers. Hegemonic masculine ideals that underpin slaughterhouse work mean that the emotions of workers as well as the emotional experience of cattle are either denied, diminished or repressed. Based on fieldwork in an Irish slaughterhouse, I articulate how the industrial slaughter of animals entangles human and non‐human life in metamorphic processes that seek t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 48 publications
0
37
0
Order By: Relevance
“…Whereas janitors are classified as "dirty workers" because of their proximity to physical dirt, McMurray and Ward proposed that distress line workers are classified as "dirty" because of their proximity to toxic or negative emotions (i.e., "emotional dirt") when working with people who are suicidal, upset, or abusive. Other examples include workers in rape crisis centers (Zilber, 2002) and slaughterhouses (McLoughlin, 2019), and border control agents (Rivera, 2015). Scholars have shown that bearing an emotional stigma can negatively affects people's wellbeing (e.g., workers in slaughterhouses, see McLoughlin, 2019).…”
Section: Sources Of Stigmamentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas janitors are classified as "dirty workers" because of their proximity to physical dirt, McMurray and Ward proposed that distress line workers are classified as "dirty" because of their proximity to toxic or negative emotions (i.e., "emotional dirt") when working with people who are suicidal, upset, or abusive. Other examples include workers in rape crisis centers (Zilber, 2002) and slaughterhouses (McLoughlin, 2019), and border control agents (Rivera, 2015). Scholars have shown that bearing an emotional stigma can negatively affects people's wellbeing (e.g., workers in slaughterhouses, see McLoughlin, 2019).…”
Section: Sources Of Stigmamentioning
confidence: 99%
“…Other examples include workers in rape crisis centers (Zilber, 2002) and slaughterhouses (McLoughlin, 2019), and border control agents (Rivera, 2015). Scholars have shown that bearing an emotional stigma can negatively affects people's wellbeing (e.g., workers in slaughterhouses, see McLoughlin, 2019). In addition, while there is only limited research on how emotional stigma impacts organizations or industries, it is reasonable to anticipate that organizations with an emotional stigma (e.g., toxic emotional culture, see Frost, 2007) would have lowered employee engagement, reduced productivity, or high levels of turnover.…”
Section: Sources Of Stigmamentioning
confidence: 99%
“…Parmar et al ( 2010 ) emphasise the interrelatedness of actors as the basis for management when discussing stakeholdership. In the instrumentally abstract ‘no care’ human–animal relationship (Connolly & Cullen, 2018 ), animals are purely seen as raw materials, objects or ‘animals-as-food’ (McLoughlin, 2019 ), rather than sentient beings. Here, conditions for animal stakeholdership are limited due to low emotional and social human–animal bonds.…”
Section: Discussion: Affective Salience In Care Informing Animal Stakeholdershipmentioning
confidence: 99%
“…Two studies examined how workers coped with the specific act of slaughtering of animals. McLoughlin (2018) posited that SHWs needed to conform to hegemonic masculinity in order to successfully complete their work. The reasoning underpinning this conformity was that emotions impeded their work, caused internal conflict, and lowered their status in the eyes of their peers.…”
Section: Key Findingsmentioning
confidence: 99%